2003
DOI: 10.1124/jpet.103.049940
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholate Reduces Ethinylestradiol Glucuronidation in the Rat: Role in Prevention of Estrogen-Induced Cholestasis

Abstract: Ethinylestradiol (EE) administration (5 mg/kg, s.c., daily for 5 days) to rats leads to cholestasis, and its derivative EE 17␤-glucuronide is a likely mediator of this effect. Coadministration of ursodeoxycholate (UDC) was shown to prevent ethinylestradiol-induced cholestasis. The aim of this study was to evaluate the inhibitory effect of UDC on EE glucuronidation in vivo and in vitro as a potential mechanism to explain UDC protection. UDC treatment (25 mg/kg, i.p., daily for 5 days) decreased the biliary excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…As shown in Table 1, neither ALT nor AST was affected by GAL administration, indicating that the protocol used to study GAL action on biliary secretory function was not toxic. Neither of these serum markers was modified by EE, in agreement with previous results (Bouchard et al, 1993;Crocenzi et al, 2001;Sanchez Pozzi et al, 2003). However, EE treatment led to a 40% increase in ALP serum activity, a biochemical marker of cholestasis (Table 1), which was not restored by GAL coadministration.…”
Section: Biliary Excretion Of Ee Metabolites Two Hours After Injectisupporting
confidence: 80%
“…As shown in Table 1, neither ALT nor AST was affected by GAL administration, indicating that the protocol used to study GAL action on biliary secretory function was not toxic. Neither of these serum markers was modified by EE, in agreement with previous results (Bouchard et al, 1993;Crocenzi et al, 2001;Sanchez Pozzi et al, 2003). However, EE treatment led to a 40% increase in ALP serum activity, a biochemical marker of cholestasis (Table 1), which was not restored by GAL coadministration.…”
Section: Biliary Excretion Of Ee Metabolites Two Hours After Injectisupporting
confidence: 80%
“…The steatotic rat model was established using female Wistar rats of ϳ250 g body weight. The procedure is a modification of the protocol given by Sanchez Pozzi and co-workers (30). Rats were housed and fed under standard conditions and were injected with 17␣-ethinylestradiol (2 mg/kg sc) on 8 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…In doing so, we also collected a range of biochemical and histological parameters to examine possible correlations. Steatosis in rats was induced by administration of 17␣-ethinylestradiol (30). Also, we sought to mimic the hepatic fatty acid accumulation and symptomatological aspects of the early stages of fatty liver disease.…”
mentioning
confidence: 99%
“…Its beneficial effect on reversion of EE-induced cholestasis is based on the improvement of the biliary secretory function impaired by the estrogen (Jacquemin et al, 1993;Sanchez Pozzi et al, 2003). It was demonstrated that UDC up-regulates canalicular Mrp2 expression in normal mice (Fickert et al, 2001) and that its taurine derivative [tauroursodeoxycholate (TUDC)] stimulates insertion of preexisting pericanalicular vesicles containing Mrp2 into the canalicular domain, thus accounting for prevention of taurolithocholate-induced cholestasis (Beuers et al, 2001).…”
mentioning
confidence: 99%
“…EE, a synthetic estrogen, induces intrahepatic cholestasis in experimental animals (Gumucio and Valdivieso, 1971;Jacquemin et al, 1993;Crocenzi et al, 2001;Sanchez Pozzi et al, 2003) by reducing the liver's capacity to excrete bile salts and organic anions (Gumucio and Valdivieso, 1971;Bossard et al, 1993). Expression of Mrp2, a canalicular transporter involved in organic anion excretion and, hence, in the formation of the bile salt-independent fraction of bile flow (Crocenzi et al, 2004), is decreased in EE cholestasis (Trauner et al, 1997).…”
mentioning
confidence: 99%